Comparison of uninterrupted direct oral anticoagulation with vitamin‐K antagonists during AF‐ablation in the clinical routine. A single center register. Issue 9 (26th July 2021) - Christoph, Marian; Youssef, Akram; Svitil, Jan; Forkmann, Mathias; Huo, Yan; Gaspar, Thomas; Francke, Alexander; Schoen, Steffen; Quick, Silvio; Wunderlich, Carsten
Abstract: Background: Uninterrupted direct oral anticoagulation (DOAC) in AF‐ablation is recommended, proven by randomized trials. The outcome and the periinterventional differences between DOACs and VKA in the real world clinical practice are discussed controversial. Hypothesis: To investigate efficiency and safety of uninterrupted DOAC therapy compared to VKA during AF‐Ablation in real world setting with a focus on periinterventional heparin dosage.